ENZYMATIC SYNTHESIS OF FRUCTO-OLIGOSACCHARIDES USING PECTINEX® ULTRA SP-L: A STUDY OF EXPERIMENTAL CONDITIONS - Simović, Milica (Food and Feed Research, 2021)
The obvious benefits of employing prebiotics as functional components in many foods and feed products have resulted in higher demand for their industrial production, necessitating the development of more efficient and cost-effective manufacturing procedures. As a result, the goal of this study was to synthesize confirmed prebiotics, namely fructo-oligosaccharides (FOS), using sucrose as a substrate, since it allows the synthesis of oligosaccharides with lower polymerization degree, and consequently, a more pronounced prebiotic effect. Due to its availability, low market price, and high stability under industrial conditions, a commercial enzymatic mixture, Pectinex® Ultra SP-L, is used as a source of enzyme – fructosyltransferase (FTase). By varying key experimental conditions such as pH, temperature, enzyme and substrate concentrations, as well as the duration of the process, the composition of the FOS mixture can be adjusted to fit the potential applications. It was found that by performing the reaction in an aqueous medium (pH 7), at a temperature of 50 °C using an enzyme concentration of 1% (v/v) and any sucrose concentration in the range of 200-700 g/L, it was possible to achieve maximum FOS yield of 60% of total carbohydrates within a 24 h. The produced syrup with a high content of FOS can be further used as an adequate food additive, or else, developed processes should be used for the transformation of various food products (such as juices, jams, fillings, candies, cakes, etc.) in which sucrose dominates, creating products with lower caloric and higher functional value.
Keywords: fructo-oligosaccharides; prebiotics; fructosyltransferase; enzymatic synthesis